POMPALI TESİSATLARDA SU DARBESİ OLAYININ AKIŞ GÖRSELLEŞTİRME YÖNTEMİYLE İNCELENMESİ - KISTAK, CELAL (Fırat Üniveristesi, 2015)
Su darbesi, kapalı boru sistemindeki ani akım değişimlerinden oluşan, istenmeyen bir durumdur. Su darbesi oluştuğu zaman, sonuçları çok ağır ve hatta ölümcül bile olabilir. Su darbesi, genellikle hidroelektrik santrallerin cebri borularında, su iletim hatlarında, su şebekelerinde vs. meydana gelir. Bu nedenle su şebekelerinin işletme prensipleri doğru bir şekilde belirlenmelidir. Bu tezde, pompalı tip tesisatlarda su darbesi sorunları akış görselleştime yöntemiyle incelenmiştir.

Waterhammer is an undesirable event that consist of sudden flow changes in a confined pipe system. When water hammer occurs, its consequences can be very costly and even sometimes deadly. In general, water hammer may be encountered in the penstocks of hydropower plants, water transmission lines, water networks etc. Therefore, the operation guidelines of the water networks should be defined correctly. In this thesis,using flow visualization techniques waterhammer problems in pumped water lines are investigated.
An experimental analysis of water hammer in pump systems using flow visualization technique
Keywords: Makine Mühendisliği